2021
DOI: 10.1016/j.asmr.2021.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Older, Heavier, Arthritic, Psychiatrically Disordered, and Opioid-Familiar Patients Are at Risk for Opioid Use After Medial Patellofemoral Ligament Reconstruction

Abstract: Purpose To investigate which factors predispose patients for prolonged opioid use after medial patellofemoral ligament (MPFL) reconstruction. Methods A retrospective review of all patients who underwent MPFL reconstruction at a single institution between January 2013 and June 2020 was conducted. Opioid consumption before and after surgery was recorded and confirmed using Michigan Automated Prescriptions System monitoring program. Patients were classified into preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Risk factors including male sex, increased body mass index, chronic preoperative opioid use, and history of anxiety/depression have been established for opioid use in pain management and length of postoperative opioid use. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 A prospective study of 250 patients (36 Black patients, 100 Hispanic patients, and 114 white patients) after open reduction and internal fixation of limb fractures by Ng et al. 37 found that Black and Hispanic patients received lower-dose analgesics during their hospitalization (average LOS of 4.45 days) than white patients (Black: 16 mg/day, Hispanic: 13 mg/day, white: 22 mg/day, P < .002).…”
Section: Health Disparities In Pain Controlmentioning
confidence: 99%
“…Risk factors including male sex, increased body mass index, chronic preoperative opioid use, and history of anxiety/depression have been established for opioid use in pain management and length of postoperative opioid use. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 A prospective study of 250 patients (36 Black patients, 100 Hispanic patients, and 114 white patients) after open reduction and internal fixation of limb fractures by Ng et al. 37 found that Black and Hispanic patients received lower-dose analgesics during their hospitalization (average LOS of 4.45 days) than white patients (Black: 16 mg/day, Hispanic: 13 mg/day, white: 22 mg/day, P < .002).…”
Section: Health Disparities In Pain Controlmentioning
confidence: 99%
“…1 Between 2000 and 2017, accidental deaths due to opioid use increased from 2.2 to 13.2 deaths per 100,000 people. 2 In particular, orthopaedic surgeons prescribe opioids at high rates. 2,3 There have been multiple studies that have investigated risk factors of opioid use after orthopaedic procedures, such as anterior cruciate ligament reconstruction, 4 meniscal surgery, 5 and hip/knee arthroplasty.…”
mentioning
confidence: 99%
“…2 In particular, orthopaedic surgeons prescribe opioids at high rates. 2,3 There have been multiple studies that have investigated risk factors of opioid use after orthopaedic procedures, such as anterior cruciate ligament reconstruction, 4 meniscal surgery, 5 and hip/knee arthroplasty. 6 Total shoulder arthroplasty (TSA) is a common orthopaedic procedure, with several advancements over the years.…”
mentioning
confidence: 99%
“… 1 Although multiple providers in various medical specialties prescribe opioids, orthopaedic surgeons do so at one of the highest rates. 1 , 2 , 3 Orthopaedic patients also have a high prescription refill rate compared with other specialties. 2 Okoli et al.…”
mentioning
confidence: 99%
“… 1 , 2 , 3 Orthopaedic patients also have a high prescription refill rate compared with other specialties. 2 Okoli et al. 4 analyzed postoperative opioid use after common outpatient orthopaedic surgeries at a single institution, some of which being rotator cuff repair, anterior cruciate ligament reconstruction (ACLR), and Achilles tendon repair, finding that more than 11% of patients continued using opioids after 6 months.…”
mentioning
confidence: 99%